Research on the Transient Hydraulic Characteristics of Multistage Centrifugal Pump During Start-Up Process - Yun, Long; Bin, Lin; Jie, Fang; Rongsheng, Zhu; Qiang, Fu (Frontiers in Energy Research, 2020)
Compared with the periodic unsteady flow induced by single-stage centrifugal pump, the internal flow state of multistage centrifugal pump is more complicated and the flow is more disordered. In this paper, the start-up process is divided into two stages: the closed-valve transition and the open-valve transition. The transient operation process is simulated numerically, and the pump characteristics and the evolution characteristics of the internal flow field are analyzed. It is found that when the impeller does the same work, compared with the steady state at the same speed, the mechanical energy in the internal flow field is converted into more kinetic energy and less pressure, which is a typical performance of the transient effect during the start-up process of the closed-valve transition. Compared with the steady state at the same flow rate, in the initial stage of the open-valve start-up phase, the stall group in the impeller flow channel is larger and the number of stall groups is more during the transient process, which exacerbates the rotational stall of the internal flow of the impeller, and the flow is more disordered. As a result, the amplitude of the hump fluctuation is greater than that under the same flow steady state.